2013
DOI: 10.1037/a0029723
|View full text |Cite
|
Sign up to set email alerts
|

Models of hemispheric specialization in facial emotion perception—a reevaluation.

Abstract: (2013) 'Models of hemispheric specialization in facial emotion perception -a reevaluation.', Emotion., 13 (1). pp. 159-167. Further information on publisher's website:https://doi.org/10.1037/a0029723Publisher's copyright statement:c 2013 APA, all rights reserved. This article may not exactly replicate the nal version published in the APA journal. It is not the copy of record.Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
59
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 78 publications
17
59
1
Order By: Relevance
“…Using the same prosodic and linguistic dichotic listening tasks as in the present study, a similar reduced LEA in the prosodic task has been found in healthy males who are high in impulsive nonconformity, a hypomanic-related personality trait (Najt et al, 2013). Healthy subjects with low impulsive non-conformity scores showed the typical LEA in this task.…”
Section: Discussionsupporting
confidence: 86%
“…Using the same prosodic and linguistic dichotic listening tasks as in the present study, a similar reduced LEA in the prosodic task has been found in healthy males who are high in impulsive nonconformity, a hypomanic-related personality trait (Najt et al, 2013). Healthy subjects with low impulsive non-conformity scores showed the typical LEA in this task.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, FER deficit could also be linked to motor asymmetries in PD, but the question of whether patients with left‐dominant motor symptoms (LPD) showing relatively greater neural degeneration in the right hemisphere have a more severe deficit than patients with right‐dominant motor symptoms remains open. LPD patients could be more likely to show FER impairments considering the relatively greater role of the right hemisphere in FER (at least for anger, fear, and sadness) and the prominence of visuospatial deficits in LPD patients 85, 86. Last, since the earliest studies, emotional disorders in PD concern both expression and recognition, and some authors have even reported positive correlations between facial expression and FER impairment 17, 37, 87, 88, 89.…”
Section: Discrepancies In Resultsmentioning
confidence: 99%
“…As previously described, the visual half-field paradigm has offered differential support for both Right Hemisphere and Valence-Specific Models (Najt et al, 2013). As Najt and colleagues point out, however, visual half-field studies have not always addressed potential language confounds.…”
Section: Discussionmentioning
confidence: 96%
“…The view that all emotions are preferentially processed by the right hemisphere independent of valence -the Right Hemisphere Hypothesis (e.g. Borod et al, 1998) -is still supported by more recent visual half-field studies (for reviews, see Mandal & Ambady, 2004;Najt, Bayer, & Hausmann, 2013). However, some research has led to alternative, and currently debated models (Abbott, Cumming, Fidler, & Lindell, 2013;Killgore & Yurgelun-Todd, 2007), describing the laterality of emotional processing: the Valence-Specific Hypothesis, that positive expressions (i.e.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation